If You Give a Mouse a Cookie - Numeroff, Laura Joffe; Bond, Felicia (New York, NY A Laura Geringer Book, an imprint of HarperCollinsPublishers, 2010)
Relating the cycle of requests a mouse is likely to make after you give him a cookie takes the reader through a young child's day.
Keywords: Mice -- Juvenile fiction; Cookies -- Juvenile fiction; Humorous Stories; Mice -- Fiction; Cookies -- Fiction; Humorous Stories